Pengaruh Penjualan Kredit Terhadap Kinerja Perusahaan Di Indonesia - Arif Darmawan; Surya Firmansyah (Department of Accounting-Faculty of Economic and Business (FEB), 2018)
This study aims to examine the effect of credit supply on sales growth and profitability in the manufacturing and trading companies in Indonesia. Least Square (LS and AR) is a statistical tool that used to analyze the panel data included 72 companies in 2010 - 2014. The variable in this study is receivable as an independent variable, growth in sales and earnings as the dependent variable, and the age and size of the company into a variable kontrol. The study provide empirical evidence that trade credit in term account receivable has no significant effect on sales growth but has significantly positively effect on profitability. This indicates that companies investing more in account receivable can increase its profitability. Furthermore, the size of the company does not have a significant effect on sales growth while the age of the company significantly negatively affect sales and profit growth.